2001
DOI: 10.1073/pnas.241508098
|View full text |Cite
|
Sign up to set email alerts
|

High rate of CAD gene amplification in human cells deficient in MLH1 or MSH6

Abstract: MutS and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 51 publications
5
43
0
Order By: Relevance
“…Similarly, we have shown that mitotic recombination is also highly dependent on DNA homology, and is much more so than is meiotic recombination (26). Further, the absence of mismatch repair alleviates a suppression of gene amplification in human cells (27), a process mediated by double-strand DNA breaks, and also renders mammalian cells hypersensitive to camptothecin, a drug that inhibits the DNA breakage-reunion activity of topoisomerase I (28). Thus, it is likely that mismatch repair modulates mitotic recombination and allows it to occur more frequently in MEFs than in ES cells.…”
Section: Discussionmentioning
confidence: 77%
“…Similarly, we have shown that mitotic recombination is also highly dependent on DNA homology, and is much more so than is meiotic recombination (26). Further, the absence of mismatch repair alleviates a suppression of gene amplification in human cells (27), a process mediated by double-strand DNA breaks, and also renders mammalian cells hypersensitive to camptothecin, a drug that inhibits the DNA breakage-reunion activity of topoisomerase I (28). Thus, it is likely that mismatch repair modulates mitotic recombination and allows it to occur more frequently in MEFs than in ES cells.…”
Section: Discussionmentioning
confidence: 77%
“…Interestingly, gene amplification has also been reported to arise in MLH1-deficient cells (10), but a direct connection between MLH1-induced and hypoxia-induced gene amplification has not been tested. Nonetheless, together these observations suggest that hypoxia can constitute a profound cellular stress that can promote genetic instability on several levels.…”
Section: Discussionmentioning
confidence: 99%
“…Our results argue that some mrt mutants are likely to contain mutations that result in increased levels of genomic damage. It also should be pointed out that the recent evidence that human cells with mismatch repair mutations have elevated rates of gene amplification (35) suggests the possibility that msh-2 worms may accumulate multiple types of genomic damage.…”
Section: Discussionmentioning
confidence: 99%